2021
DOI: 10.1108/prt-06-2021-0060
|View full text |Cite
|
Sign up to set email alerts
|

Printability of bio-composite sheets made from paper mill and cardboard mill waste sludge

Abstract: Purpose The purpose of this study is to reveal the usability of waste paper sludge on the production of composite materials and the printability of their surfaces were investigated. Design/methodology/approach First, composite plates were produced by using dried and milled waste sludge together with polyester resin and epoxy. Screen printing using water, solvent and UV-based inks were carried out. Findings It was determined that UV and solvent-based inks in both resin groups were permanently attached to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…The results indicated that 20% WP and 40% LDPE improved tensile strength (17%) and water resistance (70%), while 25% WP and 35% LDPE improved flexural properties (15%) and stiffness (145%). Another work investigated the surface printability of the epoxy or polyester + WP (sludge) or cardboard waste composite plate [ 89 ]. The prints were made with water, solvent- and UV-based inks for a single color (cyan).…”
Section: Waste Paper-polymeric Compositesmentioning
confidence: 99%
“…The results indicated that 20% WP and 40% LDPE improved tensile strength (17%) and water resistance (70%), while 25% WP and 35% LDPE improved flexural properties (15%) and stiffness (145%). Another work investigated the surface printability of the epoxy or polyester + WP (sludge) or cardboard waste composite plate [ 89 ]. The prints were made with water, solvent- and UV-based inks for a single color (cyan).…”
Section: Waste Paper-polymeric Compositesmentioning
confidence: 99%
“…The printability of the paper is related to factors such as the surface structure of the paper, topography, optical properties, printing method used, colourant used. For example, Yüce et al (2021) stated in a study that to obtain the desired colour values in printability, the colour surface to be printed should be in light colours because the printing ink to be applied to the composite surface creates sufficient colour contrast on the surface.…”
Section: Introductionmentioning
confidence: 99%
“…The printability of the paper depends on factors such as the topography of the paper, surface structure, optical properties, colorant used and printing method used. In a study, Yüce et al (2021) stated that because the printing ink to be applied to the composite surface creates sufficient color contrast on the surface, the color surface to be printed should be in light colors to obtain the desired color values in printability. In a similar study, Tutak (2017) used soybased oleic acid from soybean oil, not the oleic acid specified in the INGEDE standard, and obtained deinked papers with better optical properties.…”
Section: Introductionmentioning
confidence: 99%
“…The harmony of the colorant used with the paper surface is one of the criteria that determines the print quality. There is a printing quality difference between offset ink or inkjet ink and electrophotographic printing toner (Yılmaz et al , 2022b). Toner is a pigmented polymer composite used in electrophotographic printing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation